Changes of lactose, lactic acid, and acetic acid contents in Serra cheese during ripening - Macedo, Angela C. (2011)
Changes in the quantities of lactose, lactic acid and acetic acid in Serra cheese were monitored using a triplicate two-way factorial design over a ripening period of 35 days (sampling at 0, 7, 21 and 35 days) throughout the cheesemaking season (sampling in November, February and June). The amount of lactose in total solids of cheese (TS) decreased slowly from 6.17% to 0.21% (w/wTS) as ripening time elapsed. As a result of sugar metabolism, the lactic acid content increased from 0.07% at day 0 to 2.10% (w/wTS) by 35 days, whereas the acetic acid content increased from 0.00% to 0.24% (w/wTS) during the first week. The lactose content was statistically correlated with the lactic acid content but not with the acetic acid content.